Design as Language – a Misconception? - Vihma, Susann (FormAkademisk, 2012)
Because design is often conceived of as a language, it is worthwhile to take a closer look at this relationship. It is especially interesting to look at the transition from the verbal to the visual in interpretations and analyses of design. This article discusses some salient topics appearing in this context. In particular, claims made in the books by Kress and van Leeuwen (1996) and Krippendorff (2006) are discussed, because their approaches are widely used in design discourses, in journals, schools, exhibition catalogues, etc. These texts probably influence design research, but, in the present author’s view, do not help interpretation of visual qualities in design. The underlying critical assumption in this article is that the language metaphor and concepts derived from linguistics do not do justice to the interpretations of design objects, especially concerning their visual qualities. When these qualities are underrated, it seems difficult to assess the cultural significance of design.